Employer brand: promoting communication and language skills - Aleksandrovna, Tsareva Natalia (Universidade Estadual Paulista, 2021)
In today’s economy, the labor market is experiencing intense competition between highly qualified specialists. Russian and international companies are forced to resort to new tools for enhancing and managing staff language skills and involvement and shaping their image on the labor market. Employers use different language skills and communication tools to promote the employer brand. The study aims to investigate the means of promoting communication and language skills in staff promote the employer brand. To do so, descriptive and data gathering methods are utilized. Based on the results obtained, the most widespread and effective are social networks: modern communication channels and promotion of the employer's language skills. A program for the development of a promotion channel for the company's HR brand has been proposed. An algorithm for promoting an HR brand through targeted advertising on Instagram has been presented.